2012
DOI: 10.1128/aem.07480-11
|View full text |Cite
|
Sign up to set email alerts
|

Role of IncP-1β Plasmids pWDL7:: rfp and pNB8c in Chloroaniline Catabolism as Determined by Genomic and Functional Analyses

Abstract: Broad-host-range catabolic plasmids play an important role in bacterial degradation of man-made compounds. To gain insight into the role of these plasmids in chloroaniline degradation, we determined the first complete nucleotide sequences of an IncP-1 chloroaniline degradation plasmid, pWDL7::rfp and its close relative pNB8c, as well as the expression pattern, function, and bioaugmentation potential of the putative 3-chloroaniline (3-CA) oxidation genes. Based on phylogenetic analysis of backbone proteins, bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 64 publications
0
44
0
Order By: Relevance
“…2). Catechols are known to be the oxidation products from aniline, methylaniline, and chloroaniline (14,18,32,33), but this is the first report to have detected a major amount of catechol from aniline. Next, to prove the presence of ␥-glutamyl intermediates in aniline oxidation, we purified the GS-like protein AtdA1 and showed that it can produce ␥-GA from aniline and L-glutamate in the presence of ATP and MgCl 2 (Fig.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…2). Catechols are known to be the oxidation products from aniline, methylaniline, and chloroaniline (14,18,32,33), but this is the first report to have detected a major amount of catechol from aniline. Next, to prove the presence of ␥-glutamyl intermediates in aniline oxidation, we purified the GS-like protein AtdA1 and showed that it can produce ␥-GA from aniline and L-glutamate in the presence of ATP and MgCl 2 (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…This is strong evidence demonstrating that ␥-GA formation is the starting point of the proposed aniline oxidation mechanism (pathway). Recently, Król et al (33) reported that recombinant E. coli cells harboring only the dioxygenase genes (dcaA1A2B) from the AD gene cluster (dcaQTA1A2B) of Comamonas testosteroni produced a small amount of 4-chlorocatechol from 3-chloroaniline. Therefore, this dioxygenase may be able to attack anilines directly without GS-like and GAT-like proteins.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The two hosts, E. coli and P. putida (both belonging to the Gammaproteobacteria) were selected because the behavior of RK2 in these hosts has been relatively well studied. In addition, since IncP-1 plasmids have been found in strains within the Betaproteobacteria (for example, in the genera Achromobacter, Bordetella, Comamonas, Cupriavidus, Delftia, and Neisseria) and Alphaproteobacteria (genus Sphingomonas) (10,26,29,37,47,67,68), we also included representative hosts from those two classes: the betaproteobacterium Cupria- and M124 indicate the start methionines of TrfA-33 in RK2 and TrfA2 in pBP136, respectively. QLSLF indicates the conserved amino acid sequence motif responsible for interaction with DNA polymerase III (33).…”
Section: Methodsmentioning
confidence: 99%